Skill structure and technology structure : innovation and growth implications - Gil, Pedro Mazela (2022)
This paper builds an endogenous growth model of directed technical change with vertical and horizontal R&D and scale effects at the industry level to study an analytical mechanism that is consistent with the observed crosscountry pattern in the skill structure, the technology structure and economic growth. We calibrate the model in order to uncover the effect of the skill structure on economic growth by studying how the former affects the technology structure. We find that the small positive elasticity of the economic growth rate regarding the ratio of high- to low-skilled workers that is empirically observed is explained by the combination of moderate levels of the market complexity costs related to vertical R&D and high entry costs in the high- vis-à-vis the low-tech sectors, which dampen the positive direct effect of the absolute productivity advantage of the high-skilled workers on growth.